2020
DOI: 10.3390/cancers12092359
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mutation Patterns Reveal Melanoma Subtypes and Influence Immunotherapy Response in Advanced Melanoma Patients

Abstract: The detection of somatic driver mutations by next-generation sequencing (NGS) is becoming increasingly important in the care of advanced melanoma patients. In our study, we evaluated the NGS results of 82 melanoma patients from clinical routine in 2017. Besides determining the tumor mutational burden (TMB) and annotation of all genetic driver alterations, we investigated their potential as a predictor for resistance to immune checkpoint inhibitors (ICI) and as a distinguishing feature between melanoma subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 51 publications
2
20
0
1
Order By: Relevance
“…However, we did not observe a significant difference of OS between MYC amplification and MYC non-amplification cohorts. In addition, PDGFRA , CCND3 , KIT amplification and PTEN deletion have been reported in previous studies of MM [ 30 , 38 ], which was consistent with our findings. Deletion of the NRG1 gene was detected in 8.3% (3/36) of RMM patients and was associated with poor prognosis in our cohort.…”
Section: Discussionsupporting
confidence: 94%
“…However, we did not observe a significant difference of OS between MYC amplification and MYC non-amplification cohorts. In addition, PDGFRA , CCND3 , KIT amplification and PTEN deletion have been reported in previous studies of MM [ 30 , 38 ], which was consistent with our findings. Deletion of the NRG1 gene was detected in 8.3% (3/36) of RMM patients and was associated with poor prognosis in our cohort.…”
Section: Discussionsupporting
confidence: 94%
“…CD274 encoded PD-L1 which was one of the target for ICI and studies had suggested that patients with CD274 amplification would have better immunotherapy outcomes 33 , 34 . Current research also found that deletion of CDKN2A and alteration of PTEN increase the resistance to ICIs 35 , 36 . NOTCH2 was amplified in some patients before and after chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, genetic alterations in CDK4 pathway components (CDK4, CCND1, and CDKN2A), which are particularly common in Asians, have been associated with innate resistance to PD-1 blockade in patients with acral melanoma (93). Consistently, a recent panel-based next-generation sequencing analysis by Hilke et al (94) showed that CDKN2A deletions or loss of heterozygosity, which are commonly found in non-Caucasian patients with melanoma, were significantly enriched in patients with progressing melanomas after treatment with ICIs (nivolumab, pembrolizumab, or nivolumab plus ipilimumab).…”
Section: Current Treatment Optionsmentioning
confidence: 76%